Theories of Crime - Marsh Ian; Morgan Keith; Norris Gareth; Walkington Zoe (Routledge - Taylor & Francis Group, 2006)
Presenting a clear, comprehensive review of theoretical thinking on crime, this book encourages students to develop a deeper understanding of classic and contemporary theories, and provides an interdisciplinary approach to criminology through the contributions of sociology, psychology and biology. Preface, Crime: The Historical Context, Biological Explanations for Criminal Behaviour, Psychological Explanations for Criminal Behaviour, Sociological Explanations for Criminal Behaviour, Explaining the Criminal Behaviour of Women, Explaining the Criminal Behaviour of Ethic Minorities, References, Index.